Bioactive Potential of Brown Algae - R. R. Remya; Antony V. Samrot; S. Suresh Kumar; V. Mohanavel; Alagar Karthick; V. Kumar Chinnaiyan; Dhamodharan Umapathy; M. Muhibbullah (Adsorption Science & Technology, 2022)
Marine-derived natural products are rich source of secondary metabolites with huge potentials including novel therapeutic agents. Marine algae are considered to be a good source of secondary metabolites with versatile bioactivities. During the last few decades, researches related to natural products obtained from brown algae have remarkably escalated as they contain active compounds with varied biologically activities like antimicrobial, anticancer, antioxidant, anti-inflammatory, antidiabetic, and antiparasitic properties. The main bioactive components such as phlorotannin, fucoxanthin, alginic acid, fucoidan, and laminarin have been briefly discussed here, together with their composition and biological activities. In this review, the biological function of extracts and the metabolites of brown algae as well as their pharmacological impacts with the description of the possible mechanism of their action are described and discussed. Also, this study is expected to examine the multifunctional properties of brown algae that facilitate natural algal products, including the ability to integrate these functional properties in a variety of applications.